Conformational and electronic study of cis-peptides (non-proline residues) occurring in natural proteins - Gutierrez, Lucas Joel (2009)
First-principle computations were carried out on the conformational hyperspace of cis-peptide bond isomers of Ac-Gly-Gly-NHMe, Ac-Gly-Ala-NHMe, Ac-Ala-Gly-NHMe and Ac-Ala-Ala-NHMe. Using the concept of multidimensional conformational analysis (MDCA), geometry optimisations were performed at B3LYP/6-31G(d) level of theory, and single point energies were calculated at the B3LYP/aug-cc-pVDZ//B3LYP/6-31G(d) level of theory for the corresponding optimized structures. The relative stabilities of the various conformers were analysed using the theory of atoms in molecules. The theoretical results were compared with some experimental data (X-ray).